An ultra-thick all-diamond microchannel heat sink for single-phase heat transmission efficiency enhancement. (July 2020) - Qi, Zhina; Zheng, Yuting; Zhu, Xiaohua; Wei, Junjun; Liu, Jinlong; Chen, Liangxian; Li, Chengming
Abstract: It was predicted that diamond would play an irreplaceable role in thermal management technology at ultra-high heat flux levels owing to its outstanding thermal conductivity. In this work, an ultra-thick diamond plate, which was realized by direct-current (DC) arc jet plasma chemical vapor deposition (CVD) system, was fabricated into an all-diamond microchannel heat sink by laser. The convective heat transfer capacity, thermal resistance, device surface temperature and pressure drop of the all-diamond MCHS were systematically studied under the heat flux of 40–120 W/cm 2 based on a single-phase heat transfer system, comparing to the commercially available aluminum MCHS. Under the assumption that the extreme service temperature of the device at 100 °C, the advantage of all-diamond MCHS in reducing fluid flow is evaluated. The results demonstrated that the heat transfer coefficient of the all-diamond MCHS was in the range of 5637.10–11447.20 W/m 2 ‧K, which is 37%–73% higher than that of the aluminum MCHS with the same geometry. The volume flow of the fluid in the diamond MCHS is merely 40% of that in the aluminum MCHS could effectively reduce the equipment load owing to the significant advantage of the all-diamond MCHS in reducing the device surface temperature and thermal resistance. Highlights: An all-diamond MCHS was obtained on an ultra-thick CVD diamond plate. Diamond MCHS has the higher fin efficiency due to its superior thermal conductivity. The heat transfer coefficient of an all-diamond MCHS was 37%–73% higher than that of an aluminum MCHS. Only 40% of volume flow rate of coolant for an aluminum MCHS operation can satisfy the requirement of an all-diamond MCHS.